ASSESSMENT OF INVESTMENT ATTRACTIVENESS INDICATORS ON THE BASIS OF FACTOR ANALYSIS (World Economics and Finance Bulletin, 2023)
The paper presents the results of a factor analysis of the main socioeconomic indicators of the region. A correlation data matrix has been built. Two factors have been identified that have a significant impact on the development of the region. In conclusion, the author gives recommendations for improving the investment attractiveness of the region
Keywords: Investments; investment attractiveness; gross domestic product